Research of Inflation Processes in Ukraine in Crisis Conditions - Shynkarenko, Larysa V.; Shinkarenko, Volodymyr M.; Hostryk, Alexey M. (My University, 2022)
The purpose of the article is a research of the level of inflation in Ukraine based on the analysis of the dynamics of the annual consumer price index. In connection with the crisis phenomena in the economy, which are the consequences of the COVID-19 pandemic and Russian military aggression, the problem of restraining excessive price growth becomes the most important condition for the implementation of the socio-economic and monetary policy of the state. The impact of macroeconomic indicators such as gross domestic product, the hryvnia exchange rate against the US dollar, and the average wage in Ukraine on the growth of consumer prices is studied. With the use of application packages, it is substantiated that the dynamics of the consumer price index is characterized by a random component and cannot be approximated by elementary functions that depend only on time. With the help of MS Excel spreadsheets, a mathematical model of the dependence of the consumer price index on the rates of growth and decline of the main macroeconomic indicators was built in the form of a multiple regression equation and its adequacy was proven. Based on the constructed model, it was concluded that the exchange rate of the national currency has the greatest influence on the consumer price index. The results of the study can be used in forecasting the annual inflation rate for the next period. Forecasting of the consumer price index for 2022 was made based on the constructed model.
Shinkarenko Volodymyr M. Research of Inflation Processes in Ukraine in Crisis Conditions / Volodymyr M. Shinkarenko, Alexey M. Hostryk, Larysa V. Shynkarenko // Modeling Management of Emergent Economy : in proceedings of 10th International conference on monitoring (M3E2, 2022), 2022. - P. 156-162. DOI: 10.5220/0011932200003432
Keywords: Consumer Price Index; Multiple Regression Equation; Inflation Rate